2016
DOI: 10.1128/jvi.01597-15
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Marburg Virus VP40 Reveals a Broad, Basic Patch for Matrix Assembly and a Requirement of the N-Terminal Domain for Immunosuppression

Abstract: Marburg virus (MARV), a member of the filovirus family, causes severe hemorrhagic fever with up to 90% lethality. MARV matrix protein VP40 is essential for assembly and release of newly copied viruses and also suppresses immune signaling in the infected cell. Here we report the crystal structure of MARV VP40. We found that MARV VP40 forms a dimer in solution, mediated by N-terminal domains, and that formation of this dimer is essential for budding of virus-like particles. We also found the N-terminal domain to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
90
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(110 citation statements)
references
References 41 publications
20
90
0
Order By: Relevance
“…The cationic amino acid side chains that project away from the CTD surface provide ideal sites to form salt bridges with the anionic phospholipid head groups and mediate membrane interactions. Our data support the idea that mVP40 interactions with the membrane rely heavily on electrostatic effects, which is further supported in the structural analysis, where single mutation of Lys210 to Glu abrogated VLP formation (26). Moreover, we have demonstrated that the K210E construct binding to vesicles containing PS was ϳ30% reduced while binding of double and triple mutations of the mVP40 cationic patch was nearly fully abrogated (26).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…The cationic amino acid side chains that project away from the CTD surface provide ideal sites to form salt bridges with the anionic phospholipid head groups and mediate membrane interactions. Our data support the idea that mVP40 interactions with the membrane rely heavily on electrostatic effects, which is further supported in the structural analysis, where single mutation of Lys210 to Glu abrogated VLP formation (26). Moreover, we have demonstrated that the K210E construct binding to vesicles containing PS was ϳ30% reduced while binding of double and triple mutations of the mVP40 cationic patch was nearly fully abrogated (26).…”
Section: Discussionsupporting
confidence: 72%
“…mVP40 binding to membranes is dependent upon the anionic charge density of the plasma membrane, which when neutralized ablates mVP40 localization. The binding and cellular localization of mVP40 are consistent with recent structural analysis demonstrating that mVP40 has a flat and extensive CTD basic surface (26).…”
supporting
confidence: 73%
See 3 more Smart Citations